Inflammatory cells proliferate in the choroid and retina without choroidal thickness change in early Type 1 diabetes. (October 2020) - Campos, António; Campos, Elisa J.; Martins, João; Rodrigues, Flávia S.C.; Silva, Rufino; Ambrósio, António Francisco
Abstract: Increasing evidence points to inflammation as a key factor in the pathogenesis of diabetic retinopathy (DR). Choroidal inflammatory changes in diabetes have been reported and in vivo choroidal thickness (CT) has been searched as a marker of retinopathy with contradictory results. We aimed to investigate the early stages in the retina and choroid in an animal model of Type 1 diabetes. Type 1 diabetes was induced in male Wistar rats via a single i.p. streptozotocin injection. At 8 weeks after disease onset, CT, choroidal vascular density, VEGF and VEGFR2 expression, microglial cell and pericyte distribution were evaluated. Diabetic rats showed no significant change in CT and choroidal vascular density. A widened pericyte-free gap between the retinal pigment epithelium and the choroid was observed in diabetic rats. The immunoreactivity of VEGFR2 was decreased in the retina of diabetic rats, despite no statistically significant difference in the immunoreactivity of VEGF. The density of microglial cells significantly increased in the choroid and retina of diabetic rats. Reactive microglial cells were found to be more abundant in the choroid of diabetic rats. Evidences of the interconnection between the superficial, intermediate, and deep plexuses of the retina were also observed. At early stages, Type 1 diabetes does not affect choroidal thickness and choroidal vascular density. Proliferation and reactivity of microglial cells occurs in the choroidal stroma and the retina. The expression of VEGFR2 decreases in the retina. Highlights: Early Type 1 diabetes alters pericyte cells distribution in the inner choroid. The expression of VEGR2 decreases in the retina. Proliferation and reactivity of microglia occurs in the choroid and the retina. Choroidal thickness and vascular density do not change in early Type 1 diabetes.